Iron sensing in plants - Isabel Cristina Vélez-Bermúdez; Wolfgang Schmidt; Wolfgang Schmidt (Frontiers in Plant Science, 2023)
The ease of accepting or donating electrons is the raison d’être for the pivotal role iron (Fe) plays in a multitude of vital processes. In the presence of oxygen, however, this very property promotes the formation of immobile Fe(III) oxyhydroxides in the soil, which limits the concentration of Fe that is available for uptake by plant roots to levels well below the plant’s demand. To adequately respond to a shortage (or, in the absence of oxygen, a possible surplus) in Fe supply, plants have to perceive and decode information on both external Fe levels and the internal Fe status. As a further challenge, such cues have to be translated into appropriate responses to satisfy (but not overload) the demand of sink (i.e., non-root) tissues. While this seems to be a straightforward task for evolution, the multitude of possible inputs into the Fe signaling circuitry suggests diversified sensing mechanisms that concertedly contribute to govern whole plant and cellular Fe homeostasis. Here, we review recent progress in elucidating early events in Fe sensing and signaling that steer downstream adaptive responses. The emerging picture suggests that Fe sensing is not a central event but occurs in distinct locations linked to distinct biotic and abiotic signaling networks that together tune Fe levels, Fe uptake, root growth, and immunity in an interwoven manner to orchestrate and prioritize multiple physiological readouts.